The accidental scientist the role of chance and luck in scientific discovery - Donald, Graeme (Michael O'Mara Books, 2017)
Have you ever wondered how the ideas for some things come about? Surprisingly it is often as much down to chance as a single person's brilliance. The Accidental Scientist explores the role of chance and error in scientific, medical and commercial innovation, outlining exactly how some of the most well-known products, gadgets and useful gizmos came to be. From the jacuzzi to jeans and TNT to Tipp-Ex, this book explores many of the discoveries that we are all so familiar with today, yet have the most interesting origins because of the story behind them. Not all discoveries require brilliance, and as The Accidental Scientist demonstrates, sometimes a special ingredient is needed: luck.